Electromagnetic Waves, Materials, and Computation with MATLAB - Kalluri, Dikshitulu K. (Boca Raton, FL : CRC Press, 2012)
"Preface The subject of electromagnetics is still a core subject of the undergraduate electrical engineering (EE) curriculum; however, at most of the universities in United States, the time allotted to teach it is cut into half (one 3-credit course instead of two). The present graduates with BS degree in EE being rushed through the same curriculum content in a shorter time often miss the concepts and depend on a lot of formulas which they use as a recipe for some calculations based on an example worked out in the book. Some of them are fortunate to take a follow-up special elective course in microwaves or RF design or antennas or fiber optics, and so on, thus partly reinforcing one application area. Readily available commercial software allows them to do routine calculations and design without having a conceptual understanding of the expected solution. The commercial software is so user-friendly that we usually get a beautiful colored visualization of the solution, even if it is a wrong simulation of the physical problem. After getting one or two mild reprimands from the boss in his new employment after graduation, the new graduate realizes that he needs to have a fairly good idea of what is the appropriate model to be simulated and what qualitative result is to be expected. Though the software is very useful, it is not a substitute for a conceptual understanding of the steps involved in solving the problem. Fortunately, for him, there is probably a university which offers graduate courses and there is an instructor/professor who understands that these bright students recruited by some of the top companies are not less smart than the employees recruited by the company, say a decade or two ago"--
Keywords: Electromagnetism -- Mathematical models; Electromagnetic waves -- Computer simulation; Materials -- Electric properties; Lasers & Photonics; Microwaves; Mobile & Wireless Communications